Intrinsically Stretchable and Stable Ultra‐Deep‐Blue Fluorene‐Based Polymer with a High Emission Efficiency of ≈90% for Polymer Light‐Emitting Devices with a CIEy = 0.06. (20th October 2021) - Ni, Mingjian; An, Xiang; Bai, Lubing; Wang, Kai; Cai, Jiangli; Wang, Shengjie; He, Liangliang; Xu, Man; Liu, Heyuan; Lin, Jinyi; Ding, Xuehua; Yin, Chengrong; et al.
Abstract: The manufacture of robust ultra‐deep‐blue polymer with an intrinsic stretchability is an extreme challenge toward fabricating flexible light‐emitting optoelectronic devices. As a key precondition for the realization of the intrinsically stretchable behavior, easily interchain slippages also cause the formation of intermolecular excited states, which is negative to the color purity and the emission efficiency of blue‐emitting film and devices. Herein, a series of π‐interrupted‐conjugated alternating polymers with a robust ultra‐deep‐blue emission and intrinsically stretchable properties are demonstrated. Interestingly, the model polymers (P4, P6, and P8) present stable ultra‐deep‐blue emission with an extremely high efficiency of ≈90% and a Commission internationale de l'éclairage (CIE) coordinates of (0.15, 0.06) in solid‐state, attributed to the excellent singlet excitonic behavior without any obvious polaron formation. More importantly, significantly different to rigid π‐conjugated polymers, the model P8 film displays an efficient deep blue emission even under a tensile rate of ≈15%, associated with the densely interchain entanglement and interpenetration. Finally, preliminary P8‐based polymer light‐emitting diodes also show a stable ultra‐deep‐blue emission with a CIE of (0.15, 0.06). All results above confirm the effectiveness of the π‐interrupted‐conjugated strategy to construct a robust deep‐blue polymer with an excellent intrinsic stretchability, which is a great potential for applying in flexible light‐emitting devices. Abstract : Intrinsically stretchable and ultrastable deep‐blue fluorene‐based block polymers are obtained via a π‐conjugated‐interrupted strategy, which present deep‐blue emission with emission efficiency of ≈90%, associated with the single‐chromophore behavior. Beneficial of interchain entanglement, P8 film had a uniform morphology under a tensile rate of ≈15%. Finally, preliminary P8‐based PLEDs also present a stable ultra‐deep‐blue emission with a CIE of (0.15, 0.06).